Instant catapult steam explosion combined with ammonia water: A complex technology for detoxification of aflatoxin-contaminated peanut cake with the aim of producing a toxicity-free and nutrients retention of animal feed - Hui Xie; Lei Gao; Zhimin Li; Guotao Mao; Hongsen Zhang; Fengqin Wang; Su Shiung Lam; Andong Song (Heliyon, 2024)
Aflatoxin is one of the most toxic biotoxins found in contaminated agricultural products. It has strong mutagenicity, carcinogenesis and teratogenicity to humans and animals. In this study, instant catapult steam explosion combined with ammonia water was examined for its potential to degrade aflatoxin B1 in peanut cake in order to improve its utilization as a toxic-free animal feed. Incubation of AFB1-containing peanut cake followed by processing with Instant Catapult Steam Explosion (ICSE) led to approximately 79.03 % degradation of AFB1, while the degradation of AFB1 was up to 91.48 % under the treatment of ICSE combined with 4 % NH₃·H₂O at 1.2 MPa in 200 s of process time. After treatment, nutrients in peanut cake were not significantly changed. The toxicity of AFB1 degradation products was evaluated and the results showed that the toxicity of these products were found to be substantially less than that possessed by AFB1. A low chemical pollution, efficient and toxic-free technology system of AFB1 degradation was established, which detoxify aflatoxin-contaminated biomass for sustainable and safe utilization of agricultural biomass as animal feed.